Genome Editing Technologies for Enhancing Plant Resilience to Biotic and Abiotic Stresses - Brief Review - Mann, Anita; Ranga, Poonam; Choudhary, Priti; Yadav, Sujata; Kaul, Noyonika; Dahiya, Avni; Prakash, Nitish Ranjan; Kumar, Ashwani; Kumar, Arvind; Sanwal, Satish Kumar (Journal of Soil Salinity and Water Quality, 2024)
Global climate change is the biggest threat to the agriculture, leading to environmental stresses thereby, reducing crop quality and yield. For a sustainable food future along with demand and supply, economic accessibility to the galloping population, a 25-70% increase in agricultural productivity is sufficient. To meet these universal targets, developing climate-resilient crops will rebalance the prevailing discourse on the agricultural narrative of food security. Although, traditional plant breeding tools have uplifted the agricultural practices for developing improved crop plants but the cumbersome duration of conventional breeding limits availability of new varieties/plants for cultivation. To exaggerate this process, the recently developed technologies of genome editing, such as CRISPR/Cas9, are accurate and efficient solutions by enabling targeted alterations in plant genomes to enhance desirable traits for crop improvement. Moreover, these gene editing technologies are preferable over GM crops due to modifications in the host genome itself than the insertion of any foreign gene into it.  Additionally, the use of SDN technology for edits pertaining to SDN-1 and SDN-2 category are categorised as non-transgenic, hence, safe to use. This review is briefly compiled including evolution of different genome editing strategies, highlighting its advantages in developing crops resistant to both biotic and abiotic stresses, e.g. salt tolerance, drought resistance, and disease resistance to ensure stable food production in a changing climate.